Ischemia with no obstructive coronary artery disease (INOCA): A patient self-report quality of life survey from INOCA international. (15th January 2023) - Gulati, Martha; Khan, Najah; George, Maria; Berry, Colin; Chieffo, Alaide; Camici, Paolo G.; Crea, Filippo; Kaski, Juan-Carlos; Marzilli, Mario; Merz, C. Noel Bairey
Abstract: Background: There is limited information available regarding evidence of ischemia with no obstructive coronary arteries (INOCA) and quality of life. Purpose: To determine associations between INOCA and self-reported physical, social, and mental health. Methods: We conducted a survey of all members (n = 1579) of the INOCA International patient support group. Current self-reported diagnosis and health measures were collected. Functional capacity was retrospectively estimated using the Duke Activity Status Index (DASI), assessing levels of activities performed prior and after symptom onset. Results: A total of 297 (20.8% response rate, 91% women) reported symptoms of chest pain, pressure, or discomfort in 92.9%. Overall, 34.4% were living with symptoms for ≥3 years before an INOCA diagnosis, and 77.8% were told their symptoms were not cardiac. Estimated functional capacity was higher prior to compared to after symptom onset (8.6 ± 1.8 METs vs 5.6 ± 1.8 METs; P < 0.0001). Most respondents reported an adverse impact of symptoms on their home life (80.5%), social life (80.1%), mental health (70.4%), outlook on life (69.7%), sex life (55.9%), and their partner/spouse relationship (53.9%), while approximately three-quarters reduced their work hours or stopped work completely, 47.5% retired early, and 38.4% applied for disability. Conclusions: INOCA symptoms are associated with adverse physical, mental and social health quality of life. Increased patient awareness, physician recognition and diagnosis, and clinical trials are needed to develop evidence-based guidelines for this increasingly recognized cardiovascular disorder. Graphical abstract: Impact of Living with INOCA on Physical, Mental, Social Health & Work-Life Legend: INOCA= Ischemia with No Obstructive Coronary Arteries; METs= metabolic equivalents. Unlabelled Image Highlights: INOCA symptoms are associated with adverse physical, mental and social health quality of life. Increased patient awareness and physician recognition of INOCA are needed. Future clincial trials are needed to develop evidence-based guidelines for this increasingly recognized cardiovascular disorder.